Differentiated approach to the treatment of various forms of vulvovaginal candidiasis - T Yu Pestrikova; E A Yurasova; Yu V Voronova; T D Kovaleva; O G Scherbakova (IP Berlin A.V., 2014)
The article presents data on the results of examination and treatment of 55 patients with a diagnosis of «vulvovaginal candidiasis». In the study, the analysis of anamnestic data, and in addition, the clinical evaluation of vaginal discharge and the condition of the mucous vulva and vagina, determining pH of the vaginal environment, microscopic examination of vaginal smear, extended colposcopy is presented.After verification of the diagnosis 18 (32,73±6,33%) patients with acute uncomplicated vulvovaginal candidiasis were treated for local forms of antifungals (butokonazol), 37 (67,27±6,33%) patients with chronic complicated form of vulvovaginal candidiasis - local therapy (butokonazol), and then the system supports, suppressive therapy with fluconazole.Our results indicate that use of the drug Ginofort® (butokonazol) in patients with both acute and chronic form of vulvovaginal candidiasis yielded reliable positive therapeutic effect (p